2008
DOI: 10.1002/ppsc.200700038
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Monodisperse Micron‐Sized Droplets using Free Adjustable Signals

Abstract: This paper describes the generation of small water droplets in the size range down to a few microns. Commercially available inkjet printing devices are not suitable for producing such droplets since they produce satellite droplets. Furthermore, standard drop-on-demand devices are normally restricted to the generation of droplets with the same size as the orifice diameter. Using a new and more sophisticated computer-based signal generation system, smaller-sized droplets can be generated from the same orifice. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The set‐up for the single burning droplet experiments that has been described in detail by Rosebrock et al is shown schematically in Figure . It consists of the droplet‐on‐demand generator (piezodropper) and a square cuvette. Single monodisperse droplets are ejected upward in coflowing 0.4 L/min oxygen (purity 99.95%) and ignited by a synchronized spark discharge.…”
Section: Methodsmentioning
confidence: 99%
“…The set‐up for the single burning droplet experiments that has been described in detail by Rosebrock et al is shown schematically in Figure . It consists of the droplet‐on‐demand generator (piezodropper) and a square cuvette. Single monodisperse droplets are ejected upward in coflowing 0.4 L/min oxygen (purity 99.95%) and ignited by a synchronized spark discharge.…”
Section: Methodsmentioning
confidence: 99%
“…Isolated monodisperse droplets are produced with a piezoelectric generator (piezodropper) 27,28 at a frequency of 4 Hz . The separation distance of two successive d 0 5100 lm droplets is s51875 d 0 , which diminishes droplet interference that would otherwise occur for s 100 d 0 in normal air 29 and elevated oxygen concentrations.…”
Section: Experimental Layoutmentioning
confidence: 99%
“…In order to image a droplet, the droplet ejection was triggered with the camera [14] using the software package Motion Studio (IDT, Lommel, Belgium, version: 2.09, 2011). For the purpose of achieving a 10.5 mm x 8.4 mm field of view (FOV), which is necessary for tracking and analyzing the smallest spray droplets as found in the real spray application, a K2/SC long-distance microscope lens (Infinity, USA) was selected [15].…”
Section: Image Acquisition Systemmentioning
confidence: 99%